Complexes of N-(4-Methoxy-benzilidene)-2-(4-aminophenyl) Benzimidazole with Zn(II), Cd(II) and Hg(II) Halides - Rekha, S.; Nagasundara, K.R. (Asian Journal of Chemistry, 2016)
The synthesis and characterization by elemental analysis, conductivity measurements, IR and proton NMR spectroscopy of complexes of the Schiff base derived from 2-(4-arninophenyl) benzimidazole and 4-methoxy benzaldehyde with Zn(II), Cd(II) and Hg(II) halides have been reported. Mercury halides yield complexes with the general formula [Hg(POM4APBI)2X2]; X = Cl, Br. Zinc and cadmium halides yield binuclear complexes with the general formula [(POM4APBI)X2]; M = Zn, X = Cl; M = Cd, X = CI, Br. The complexes are all non-electrolytes and the ligand acts as a monodentate.